Glucocentric Drugs in Cardiovascular Disease Protection and Heart Failure - Khawaja M. Talha; Gregg C. Fonarow; Salim S. Virani; Javed Butler (Methodist DeBakey Cardiovascular Journal)
Evidence for cardiovascular outcomes with older-generation antihyperglycemic drugs in the management of type 2 diabetes is based on aggregated data from prior randomized controlled trials and observational studies that were not focused on prespecified cardiovascular end points. Newer antihyperglycemic medications have undergone a rigorous evaluation of cardiovascular outcomes through randomized controlled trials since the US Food and Drug Administration imposed a mandatory requirement for all glucose-lowering drugs in 2008. The three classes of drugs that have been most extensively studied are dipeptidyl peptidase 4 inhibitors, glucagon-like peptide 1 receptor agonists, and sodium-glucose cotransporter-2 (SGLT2) inhibitors, the latter two reporting significant reductions in adverse cardiovascular outcomes independent of their glycemic effect. Remarkably, it was the evidence from SGLT2 inhibitors cardiovascular outcome trials that prompted further evaluation of the drug class in patients with heart failure irrespective of their diabetes status, demonstrating a broader cardiometabolic effect of these drugs. In this review, we assess the evidence for cardiovascular outcomes with common older- and newer-generation glucose-lowering drugs in the management of type 2 diabetes. We also discuss emerging glucose-lowering drugs with novel metabolic targets that influence the risk of adverse cardiovascular events and expand on the role of these drugs beyond the management of type 2 diabetes.